Clinical Symptomatology of Anxiety and Family Function in Adolescents—The Self-Esteem Mediator - Ignatia Farmakopoulou; Maria Lekka; Evgenia Gkintoni (Children, 2024)
Background: Family, the child’s first environment, shapes their psycho-emotional balance. The literature links adolescent anxiety to family relationships, interactions, and dynamics. The self-esteem of adolescents appears to protect their mental health. Goal: This study examines whether family cohesion and adaptability affect adolescent anxiety symptoms. It also examines whether teen self-esteem mediates this relationship. Method: This cross-sectional, descriptive study included 166 Attica youth aged 12–18 from schools and educational units. The adolescents completed Olson’s FACES-III cohesion and adaptability scale, Spielberger’s STAI-C, Rosenberg’s self-esteem scale, and a socio-demographic questionnaire. Results: Family cohesion, but not adaptability, was negatively correlated with state (rho = −0.25, p = 0.001) and trait (rho = −0.46, p < 0.001) anxiety in the adolescents. Teenagers from extreme families with the lowest cohesion and adaptability had higher trait anxiety (x2(2) = 6.91, p = 0.032) than those from moderately balanced/balanced families. Self-esteem mediated the relationship between the family cohesion functioning and adolescent’s state anxiety (p = 0.005) and trait anxiety (p = 0.011). Conclusions: The findings show that family dysfunction negatively impacts adolescent anxiety, as well as their self-esteem, which protects mental balance.